Bolivia since the Bolivarian Revolution to the government of Evo Morales - Casalino Sen, Carlota Alicia (2015)
This article analyses the Bolivian political process in historical perspective since 1952. The role played by United States and Soviet Union during this long period is analyzed by taking into consideration three important concepts: political instability, failed state, and external intervention. The Bolivian political history sheds light on various aspects that must be considered in the study of the Latin American region. For example, the capacity of the state, the revolutionary stages, and how Bolivia has built its own way to establish inclusive institutions.